ANALISIS PEMBERIAN ZAKAT KEPADA SABILILLAH DALAM KONTEKS KLASIK DAN MODERN - Qothrunnada, A. Izka; Firmansyah, Mu’min (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2024)
This research discusses the definition and application of zakat "fî sabilillah" in traditional and contemporary Islamic contexts, as well as its impact on the allocation of zakat funds in modern society. The definition of zakat comes from the Arabic "zaka," which means blessing and cleanliness, while "fi sabilillah" refers to devotion in the way of Allah, both in the context of war and social and economic development. In classical times, zakat for "fi sabilillah" was primarily allocated for military purposes, but contemporary scholars broaden its meaning to include various forms of social contribution and religious education. Through case studies in Indonesia and other Muslim-majority countries, this research highlights the differences in interpretation and application of zakat "fi sabilillah" by da'wah organizations and zakat management institutions. The results of the analysis show that flexibility in the interpretation of Islamic law allows the allocation of zakat funds that are more varied and relevant to the current social conditions and needs of the people. Thus, this research provides a deeper view of the importance of adaptation and inclusiveness in zakat management to improve the welfare of Muslims at large. Penelitian ini membahas definisi dan penerapan zakat "fi sabilillah" dalam konteks tradisional dan kontemporer Islam, serta dampaknya terhadap alokasi dana zakat dalam masyarakat modern. Definisi zakat berasal dari bahasa Arab "zaka," yang berarti berkah dan bersih, sementara "fi sabilillah" merujuk pada pengabdian di jalan Allah, baik dalam konteks perang maupun pengembangan sosial dan ekonomi. Dalam zaman klasik, zakat untuk "fi sabilillah" terutama dialokasikan untuk kepentingan militer, tetapi ulama kontemporer memperluas maknanya untuk mencakup berbagai bentuk kontribusi sosial dan pendidikan agama. Melalui studi kasus di Indonesia dan negara mayoritas Muslim lainnya, penelitian ini menyoroti perbedaan interpretasi dan penerapan zakat "fi sabilillah" oleh organisasi dakwah dan lembaga pengelola zakat. Hasil analisis menunjukkan bahwa fleksibilitas dalam interpretasi hukum Islam memungkinkan alokasi dana zakat yang lebih bervariasi dan relevan dengan kondisi sosial dan kebutuhan umat saat ini. Dengan demikian, penelitian ini memberikan pandangan yang lebih mendalam tentang pentingnya adaptasi dan inklusivitas dalam pengelolaan zakat untuk meningkatkan kesejahteraan umat Islam secara luas.